Enhancement of Methane Concentration by Removing Contaminants from Biogas Mixtures Using Combined Method of Absorption and Adsorption - Muhammad Rashed Al Mamun; Shuichi Torii (International Journal of Chemical Engineering)
We report a laboratory scale combined absorption and adsorption chemical process to remove contaminants from anaerobically produced biogas using cafeteria (food), vegetable, fruit, and cattle manure wastes. Iron oxide (Fe2O3), zero valent iron (Feo), and iron chloride (FeCl2) react with hydrogen sulfide (H2S) to deposit colloidal sulfur. Silica gel, sodium sulfate (Na2SO4), and calcium oxide (CaO) reduce the water vapour (H2O) and carbon dioxide (CO2). It is possible to upgrade methane (CH4) above 95% in biogas using chemical or physical absorption or adsorption process. The removal efficiency of CO2, H2S, and H2O depends on the mass of removing agent and system pH. The results showed that Ca(OH)2 solutions are capable of reducing CO2 below 6%. The H2S concentration was reduced to 89%, 90%, 86%, 85%, and 96% for treating with 10 g of FeCl2, Feo (with pH), Fe2O3, Feo, and activated carbon, respectively. The H2O concentration was reduced to 0.2%, 0.7%, 0.2%, 0.2%, and 0.3% for treating raw biogas with 10 g of silica gel and Na2SO4 for runs R1, R2, R3, R4, and R5, respectively. Thus, given the successful contaminant elimination, the combined absorption and adsorption process is a feasible system for biogas purification.